2019
DOI: 10.11646/zootaxa.4604.2.8
|View full text |Cite
|
Sign up to set email alerts
|

First record and new species of the parasitoid wasp Chaenotetrastichus Graham (Hymenoptera: Eulophidae) for the Neotropical Region, with notes on its biology and a key for the species of the genus

Abstract: Chaenotetrastichus neotropicalis sp. nov. from the Atlantic Forest, Brazil, is described and illustrated. This new species is associated with a species of the pompilid wasp Auplopus Spinola (Hymenoptera: Pompilidae) and it represents the first record of the genus for the Neotropics. A key for the extant species of the genus Chaenotetrastichus Graham is also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 864 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…They act as endo or cleptoparasites (there are not precise observations and the behaviour of this species could not be recorded here) and this is the first record of Caenochrysis crotonis as parasitoid of Auplopus nests, as well as, the first record of this species for the Atlantic Forest domain. Also, the study conducted in the area discovered a new species for Science, the parasitoid Chaenotetrastichus neotropicalis (Marinho et al, 2019), which shows the importance of inventories in urban areas and how these areas may support still unknown hymenopteran fauna. Studies with higher number of nests collected recorded several natural enemies of pre-existing cavity nesters (Gazola & Garófalo, 2009;Rocha-Filho et al, 2017), and such cleptoparasites species are indicative of environmental quality (Sheffield et al, 2013), since their populations are the first to be affected for any habitat disturbance.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…They act as endo or cleptoparasites (there are not precise observations and the behaviour of this species could not be recorded here) and this is the first record of Caenochrysis crotonis as parasitoid of Auplopus nests, as well as, the first record of this species for the Atlantic Forest domain. Also, the study conducted in the area discovered a new species for Science, the parasitoid Chaenotetrastichus neotropicalis (Marinho et al, 2019), which shows the importance of inventories in urban areas and how these areas may support still unknown hymenopteran fauna. Studies with higher number of nests collected recorded several natural enemies of pre-existing cavity nesters (Gazola & Garófalo, 2009;Rocha-Filho et al, 2017), and such cleptoparasites species are indicative of environmental quality (Sheffield et al, 2013), since their populations are the first to be affected for any habitat disturbance.…”
Section: Discussionmentioning
confidence: 95%
“…Specimens emerged were sexed, pinned and labelled and the species identification was made by using the following keys: Mitchell (1930) Hanson & Gauld (2006), Michener (2007), Nemésio (2009), and Marinho et al (2019). Additionally, experts confirmed the identifications as stated in the acknowledgement section.…”
Section: Field Methods and Data Collectionmentioning
confidence: 99%
“…brasiliensis, C. crotonis probably feeds on the larva after it pupates, since the parasitoids were observed developing inside the cocoon of A. cf. brasiliensis (Marinho et al, 2019), and no trace of the spider was observed in the cell. This record of parasitoidism contrasts with reports by Vidal (1996), which state that species of Chaenotetrastichus are cleptoparasites.…”
Section: Discussionmentioning
confidence: 88%
“…One cell was opened (the broken cell in Fig. 4; the same brood cell is displayed in Marinho et al (2019), Figs. 14-15, with the cocoon of the host full of several parasitoid pupae).…”
Section: Auplopus Cf Rufipesmentioning
confidence: 99%
“…On the other hand, Caenochrysis crotonis has been documented for its nesting habitats, also parasitizing other Pompilidae species, such as Auplopus cf. brasiliensis (Marinho et al, 2019). This species belongs to the Chrysididae family and it can be considered a kleptoparasite as their larvae feed on food stored by their hosts (spiders, in general) (Marinho et al, 2019).…”
Section: Discussionmentioning
confidence: 99%